Plasma resistance to activated protein C regulates the activation of coagulation induced by thrombolysis in patients with ischaemic heart disease. Issue 2 (February 1997) - Pedersen, O. D.; Gram, J.; Jespersen, J.
Abstract : OBJECTIVE: To determine whether there was a relation between plasma resistance to activated protein C and the coagulation activation induced during thrombolysis with 100 mg alteplase in 25 patients with acute ischaemic heart disease. METHODS: Blood samples were collected before (t = 0 h), during (t = 2.25 h), and after (t = 4 h, t = 12 h, and t = 24 h) thrombolysis to examine the relation between baseline activated protein C resistance ratio and markers of coagulation activation-that is, thrombinantithrombin III-complexes and prothrombin fragment 1 + 2 generated during thrombolysis. RESULTS: There was a negative correlation between activated protein C resistance ratio and area under the curve of thrombin-antithrombin III-complexes (rs = - 0.60; P < 0.003) and there was a trend to a negative correlation between activated protein C resistance ratio and area under the curve of prothrombin fragment 1 + 2 (rs = - 0.37; P = 0.07). This accorded with the negative correlation between activated protein C resistance ratio and the peak value of thrombin-antithrombin III-complexes (rs = - 0.55; P < 0.005) and between activated protein C resistance ratio and the peak value of prothrombin fragment 1 + 2 (rs = - 0.42; P < 0.04). Components of the protein C/S system or known inhibitors of activated protein C may influence the activated protein C resistance ratio. There were no associations between the activated protein C resistance ratio and protein C, protein C inhibitor, or plasminogen activator inhibitor type-1, whereas there was a trend to a negative correlation between activated protein C resistance ratio and protein S. CONCLUSIONS: The results indicate that plasma resistance to activated protein C may be one of the main mechanisms regulating the activation of coagulation induced by thrombolysis. This study suggests that it may be possible to single out individuals with a high risk of reocclusion before the start of thrombolytic therapy.